인도네시아 아동들의 아침식사하기에 영향을 미치는 요인 분석 -건강신념모델을 이용하여 - 강란이(Ran Yi Kang); 이수진(Soo Jin Lee); 류호경(Ho Kyung Ryu) (Korean journal of community nutrition, 2020)
Objectives: This study investigates the current state of consuming breakfast among elementary school students residing in Malang, East Java, Indonesia, and to identify factors that influence breakfast behavior. Methods: The research model was set up as per the health belief model, and slightly modified by adding the subjective normative factors of the theory of planned behavior. The survey was conducted from July 17 to August 15, 2017 using a questionnaire, after receiving the permission PNU IRB (2017_60_HR). Results: The subjects were 77 boys (49.4%) and 79 girls (50.6%) suffering from malnutrition with anemia (21.2%) and stunting ratio of Height for Age Z Score (HAZ) (11.5%). Furthermore, moderate weakness (14.8%) and overweight and obesity (12.3%) by Body Mass Index for Age Z Score (BMIZ) were coexistent. According to the results obtained for breakfast, 21.8% did not eat breakfast before school, with 18.8% of the reasons for skipping breakfast being attributed to lack of food. Even for subjects partaking breakfast, only about 10% had a good balanced diet. The average score of behavioral intention on eating breakfast was 2.60 ± 0.58. The perceived sensitivity, perceived severity, perceived benefits, and self-efficacy of the health belief model correlated with breakfast behavior. Of these, self-efficacy (β=0.447, R2=0.200) and perceived sensitivity (β=0.373, R2=0.139) had the greatest effect on breakfast behavior. Mother was the largest impact person among children. Conclusions: In order to increase the level of breakfast behavior intention among children surveyed in Indonesia, we determined the effectiveness by focus on education which helps the children recognize to be more likely to get sick when they don't have breakfast, and increase their confidence in ability to have breakfast on their own. We believe there is a necessity to seek ways to provide indirect intervention through mothers, as well as impart direct nutrition education to children.